778 Preclinical study using a glutamatergic signaling and immune-checkpoint inhibitors in a spontaneous melanoma prone mouse model. (9th November 2020) - Eddy, Kevinn; Marinaro, Christina; Rasheed, Maryam; Campagnolo, Joseph; Zhong, Xiaoxuan; Eddin, Mohamad; Shah, Raj; Gupta, Kajal; Diaz, Jesus; Zloza, Andrew; Chen, Suzie
Abstract : Background: Much progress has been made in understanding melanoma pathogenesis within the last few years through targeted therapies and immunotherapies. However, resistance to small molecule inhibitors remains an obstacle. Immunotherapies such as checkpoint inhibitors against PD-1/PD-L1 lead to durable responses but only in a subset of melanoma patients. Mouse models reflecting human cancers provide invaluable tools towards the translation of basic science discoveries to clinical therapies, but many of these in vivo studies are short-term and do not accurately mimic patient circumstances. Our lab has a melanoma-prone transgenic mouse model which is driven by ectopic expression of a normal neuronal receptor, metabotropic glutamate receptor 1 (GRM1). This mouse model recapitulates melanoma development and progression frequently associated with melanoma patients, where aberrant GRM1 expression is detected. We have shown that in >90% of late-stage melanoma patients, there is atypical GRM1 mediated signaling and expression. Methods: In this study, we are using these mice, TGS, to determine the long-term, 18-week, therapeutic consequences of troriluzole, a prodrug for riluzole, which is an inhibitor of glutamatergic signaling plus anti-PD-1, an immune-checkpoint inhibitor. Tumor burden is monitored every 6 weeks for 18 weeks using a small imaging system, IVIS and tumor burden is quantified using ImageJ software. Blood, lymphoid, and tumor samples were collected at several time points during the study for molecular, and immune analyses. Results: Preliminary results suggest a gender-biased treatment response and that the combination of troriluzole and anti-PD-1 is more efficacious than either agent alone. In males, a 43.9% reduction in tumor burden was observed while in females there was a 29.6% increase in tumor burden in the combination group compared to vehicle. In concordance, after the removal of the treatment modality, the male mice in the combinatorial group survived 42 days longer compared to vehicle controls with sustained tumor reduction by 68.3%. In female mice no significant advantage in survival or reduction in tumor burden was noted. Conclusions: N/A